IDENTIFICATION OF THE RELATIONSHIP BETWEEN BODY MASS INDEX AND HbA1c IN TYPE 2 DM PATIENTS - Eka Nur So'emah; Emyk Windartik (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2024)
People with DM (diabetics) will generally experience obesity as a manifestation of metabolic changes in insulin and leptin hormones. The high variation in body weight and height and the many problems of controlling blood sugar levels in people with diabetes mellitus, researchers want to identify the relationship between Body Mass Index and HbA1c in Type 2 Diabetes Mellitus Patients at Bangil Hospital. This study uses correlation analytics with a cross-sectional approach to determine the relationship between body mass index and HbA1c levels in patients with type 2 diabetes mellitus at Bangil Hospital using consecutive non-random sampling techniques totalling 80 respondents. Data collection was carried out by means of laboratory examinations to see HbA1c data and blood glucose levels, while data regarding the patient's Body Mass Index (BMI) was taken by measuring body weight and height. The results of bivariate analysis conducted with the Chi-Square test approach showed that there was a significant relationship between body mass index and HbA1c (p-value = 0.000; α < 0.05). HbA1c is the gold standard for assessing blood glucose homeostasis. HbA1c is a single accurate test to assess long-term glycaemic status and is useful in all types of DM. One of the efforts that can be done to reduce blood glucose levels is by achieving good nutritional status through BMI.